Integral sliding mode controller for precise manoeuvring of autonomous underwater vehicle in the presence of unknown environmental disturbances - Kim, Minsung; Joe, Hangil; Kim, Jinwhan; Yu, Son-cheol (International journal of control, 2015)
We propose an integral sliding mode controller (ISMC) to stabilse an autonomous underwater vehicle (AUV) which is subject to modelling errors and often suffers from unknown environmental disturbances. The ISMC is effective in compensating for the uncertainties in the hydrodynamic and hydrostatic parameters of the vehicle and rejecting the unpredictable disturbance effects due to ocean waves, tides and currents. The ISMC is comprised of an equivalent controller and a switching controller to suppress the parameter uncertainties and external disturbances, and its closed-loop system is exponentially stable. Numerical simulations were performed to validate the proposed control approach, and experimental tests using Cyclops AUV were carried out to demonstrate its practical feasibility.